PENERAPAN TEKNIK KONSELING RET UNTUK MEMINIMALISIR PERILAKU BULLYING DI SMP X - Al Amin, Rizky Khoiril; Tri Damayanti, Rani; Nur Kholifatun Jannah, Aisyah; Mu'taz Gibraltar, Qais (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
This research was motivated by the large number of students who committed disciplinary violations at school. So it is an interesting problem for the author to use as a research title because it is related to the smoothness of the teaching and learning process and the success of students' learning. One of the disciplinary violations often committed by SMP X students is bullying friends, both individually and in groups, and there are many other violations. Therefore, special assistance is needed, namely group counseling services so that students' problems can be resolved. One of the techniques used to change the behavior of undisciplined students at school is the Rational Emotive Therapy (RET) technique with the hope of changing inappropriate behavior into behavior that is in accordance with school rules and regulations. The aim of this research is to find out how to apply group counseling using the Rational Emotive Therapy (RET) technique in dealing with student disciplinary violations at SMP X. The method used in this research is a literature study. The object of research is students who violate school rules and regulations. The samples that will be used as research are students in grades VII, VIII and IX.